Seeking another rationality - Felício, Munir Jorge (2021)
Fighting to emancipate the territory constitutes a continuous and procedural confrontation where new knowledge and new identities are constructed, modified, and replaced aiming to expose the knowledge and identities imposed from above to maintain the functioning of the existing order and consolidate economic rationality. The main objective of this text is to seek alternatives to this rationality, knowing of its hegemony and comprehensiveness. To construct another rationality, the emancipatory alternatives of the Global South will point out the possibility of living and producing life in another way to face the new forms of domination.